2019
DOI: 10.1007/s00262-019-02358-0
|View full text |Cite
|
Sign up to set email alerts
|

Editing the immunopeptidome of melanoma cells using a potent inhibitor of endoplasmic reticulum aminopeptidase 1 (ERAP1)

Abstract: The efficacy of cancer immunotherapy, including treatment with immune-checkpoint inhibitors, often is limited by ineffective presentation of antigenic peptides that elicit T-cell-mediated anti-tumor cytotoxic responses. Manipulation of antigen presentation pathways is an emerging approach for enhancing the immunogenicity of tumors in immunotherapy settings. ER aminopeptidase 1 (ERAP1) is an intracellular enzyme that trims peptides as part of the system that generates peptides for binding to MHC class I molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 79 publications
4
50
0
1
Order By: Relevance
“…Additional studies could be useful to verify this hypothesis, by investigating experimentally the role of proteasome and other proteases like ERAP1 on the generation of the peptidome, following for example the work of Admon et al (10, 49, 74). A very recent publication on ERAP1 inhibition showed that the average predicted affinity of MHC-I binding peptides was enhanced, by reducing presentation of sub-optimal long peptides and increasing presentation of many high-affinity 9–12-mers, suggesting that baseline ERAP1 activity in this cell line (A375, melanoma cells) is destructive for many potential epitopes (74).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies could be useful to verify this hypothesis, by investigating experimentally the role of proteasome and other proteases like ERAP1 on the generation of the peptidome, following for example the work of Admon et al (10, 49, 74). A very recent publication on ERAP1 inhibition showed that the average predicted affinity of MHC-I binding peptides was enhanced, by reducing presentation of sub-optimal long peptides and increasing presentation of many high-affinity 9–12-mers, suggesting that baseline ERAP1 activity in this cell line (A375, melanoma cells) is destructive for many potential epitopes (74).…”
Section: Resultsmentioning
confidence: 99%
“…Additional studies could be useful to verify this hypothesis, by investigating experimentally the role of proteasome and other proteases like ERAP1 on the generation of the peptidome, following for example the work of Admon et al (10, 49, 74). A very recent publication on ERAP1 inhibition showed that the average predicted affinity of MHC-I binding peptides was enhanced, by reducing presentation of sub-optimal long peptides and increasing presentation of many high-affinity 9–12-mers, suggesting that baseline ERAP1 activity in this cell line (A375, melanoma cells) is destructive for many potential epitopes (74). Based on the published results we hypothesize that the edited immunopeptidome in ERAP1 inhibited melanoma cells could still present a helix enrichment because: (1) ERAP1 inhibition increased the presentation of 9–12-mers peptides which were found in our study to show higher helical content when compared to longer peptides; (2) ERAP1 inhibition increased the frequency of N-terminal AA such as ALA, LEU, TYR, and MET which are all known to have a high helical propensity; (3) the inhibition does not affect the basic sequence motifs of the presented peptides.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have already demonstrated significant effects of ERAP1 down-regulation on the immunopeptidome of cells and have associated these changes with alterations of adaptive immune responses in autoimmunity and cancer (13). Furthermore, pharmacological regulation of ERAP1 activity is an emerging approach for cancer immunotherapy and thus a deep mechanistic knowledge on how ERAP1 regulates the immunopeptidome is crucial for optimizing potential therapies (46) (47).…”
Section: Discussionmentioning
confidence: 99%
“…Although ERAP1 has been extensively studied for its ability to generate antigenic peptides from N-terminally elongated precursors, it can also over-trim antigenic peptides to lengths not suitable for binding onto MHCI, essentially destroying the epitope (3). Recent analysis on the effect of ERAP1 on the immunopeptidome of cells have suggested that the destructive properties of ERAP1 may have been underestimated and could actually be the dominant function of the enzyme (47,52,53). The data presented herein highlight the ability of MHCI to protect peptides from ERAP1mediated degradation and are thus consistent with the hypothesis that ERAP1 acts to limit available peptides for MHCI.…”
Section: Discussionmentioning
confidence: 99%
“…The broader activity and/or selectivity of these ligands needs to be considered (Talma et al, 2019). It is an interesting feature that these peptidomimetic transition state analogs possess intracellular activity also (Koumantou et al, 2019).…”
Section: Isoform Hopping-endoplasmic Reticulum Aminopeptidasementioning
confidence: 99%